(untitled) (Palimpsesto, 2016)
In the first decades of twenty-century, changes in ideology of pregress and new development of mass culture, are both process wich determine the transnational knowledge of modernity and contemporary meanings of technology. Radio, as aural comunication device through electrics waves, involve the arrival of sound in arrangement of time and daily life, as well as his ability for change the meanings of space and distance. These new properties of technology were assimilated, interpreted and disseminated through the translation of radiophonic technics in several discourse about sound and communication in the modern press.